PSS Design Based on Fuzzy Controller with Particle Swarm Optimization Tuning - Ermanu A. Hakim; Nur Kasan; Nurhadi Nurhadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
The research was conducted for implementing of PSS (Power system stabilizer) which was designed based on the fuzzy logic controller (FLPSS). This approach has a main purpose for stabilizing and improving the damping of synchronous machine. The speed and active power deviation were used as fuzzy controller's inputs. The controller's output was forwarded into AVR subsequently. In order to achieve optimal setting, the optimal criteria of the Integral of Time were multiplied by the Absolute Error (ITAE). The performance of the proposed PSS under small disturbances, system parameters and loading conditions was tested. The experiment's results showed the usefulness of the specified method for damping out the system oscillations.